Convergent Evolution of Ergothioneine Biosynthesis in Cyanobacteria. (2nd October 2017) - Liao, Cangsong; Seebeck, Florian P.
Abstract: Biosynthesis of N ‐α‐trimethyl‐2‐thiohistidine (ergothioneine) is a frequent trait in cyanobacteria. This sulfur compound may provide essential relief from oxidative stress related to oxygenic photosynthesis. The central steps in ergothioneine biosynthesis are catalyzed by a histidine methyltransferase and an iron‐dependent sulfoxide synthase. In this report, we present evidence that some cyanobacteria recruited and adapted a sulfoxide synthase from a different biosynthetic pathway to make ergothioneine. The discovery of a second origin of ergothioneine production underscores the physiological importance of this metabolite and highlights the evolutionary malleability of the thiohistidine biosynthetic machinery. Abstract : Two paths, one destination : Biosynthesis of N ‐α‐trimethyl‐2‐thiohistidine (ergothioneine) is a frequent trait in cyanobacteria. Evidence is presented of convergent evolution of ergothioneine biosynthesis. Ancient cyanobacteria may have adapted an ovothiol biosynthetic enzyme to produce ergothioneine as a response to changing environmental conditions.